1981
DOI: 10.1038/bjc.1981.197
|View full text |Cite
|
Sign up to set email alerts
|

Differential immune reactivity of tumour-intrinsic and peripheral-blood lymphocytes against autoplastic colorectal carcinoma cells

Abstract: Summary.-Peripheral blood lymphocytes (PBL) were obtained from 13 patients and tumour-intrinsic lymphocytes (TIL) from 20 patients with colorectal cancer. The PBL were separated on a Ficoll-Isopaque gradient and the TIL by digestion of the tumour with collagenase-DNase. Both PBL and TIL were passed through nylonwool columns and the eluted cells were co-cultured for 2 h with 51Cr-labelled tumour cells from the same patient. If patients in whom spontaneous 51Cr release from the tumour cells was greater than 3300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…However, the immune defence, if it was ever raised, appears to have deteriorated at least locally by the time tumours develop into clinically detectable lesions. This is in good agreement with the generally found suppression of various immune activities of tumour-infiltrating mononuclear cells (MNCs) (Nind et al, 1973;Klein et al, 1980;Bland et al, 1981;Hutchinson et al, 1981;Vose et al, 1981Vose et al, , 1982Vose and Moore, 1985;Miescher et al, 1986). Such immunosuppression may be mediated by tumour-derived factors or subsets of MNC.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…However, the immune defence, if it was ever raised, appears to have deteriorated at least locally by the time tumours develop into clinically detectable lesions. This is in good agreement with the generally found suppression of various immune activities of tumour-infiltrating mononuclear cells (MNCs) (Nind et al, 1973;Klein et al, 1980;Bland et al, 1981;Hutchinson et al, 1981;Vose et al, 1981Vose et al, , 1982Vose and Moore, 1985;Miescher et al, 1986). Such immunosuppression may be mediated by tumour-derived factors or subsets of MNC.…”
supporting
confidence: 75%
“…This may indicate that the local immunosuppression is reversible (Klein et al, 1980;Hutchinson et al, 1981;Vose and Moore, 1985;Rosenberg et al, 1986). …”
mentioning
confidence: 99%
“…Until recently, functional studies of human TIL were not feasible due to the paucity of these cells in tumor cell suspensions [22]. In a few cases where it was possible to examine proliferative and cytotoxic activities of human TIL, they were found to be depressed [4,9,11]. More recent availability of a T cell growth factor (TCGF) facilitated studies of human TIL and their in vitro culture [21].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive testing of similar freshly derived tumourcell suspensions has shown that they are largely refractory to NK-mediated lysis and minimally express the relevant recognitive structure (Vose & Moore, 1980). As such they share with the short-term cultures of Nairn and associates (Nairn et al, 1971;Pihl et al, 1976) the property of permitting the measurement of specific effector function (Werkmeister et al, 1979 (Hutchinson et al, 1981). 58 In situ there is evidence that these cells have suppressor activity, and are less responsive to mitogens than PBL (Vose & Moore, 1979).…”
Section: Discussionmentioning
confidence: 99%